Analisis Frasa Endosentrik dalam Teks Cerita Hikayat pada Buku Bahasa Indonesia Kelas X Kurikulum Merdeka - Nur Saidah; Farida Ainur Rohmah; Ainun Rahma Dani; Asep Purwo Yudi Utomo; Turahmat; Nina Queena Hadi Putri (Student Research Journal, 2023)
This study aims to determine the use of endocentric phrases as well as describe fragments of phrases contained in the Hikayat text in the Buku Bahasa Indonesia Kelas X Kurikulum Merdeka. This study uses a theoretical approach, namely syntax, and a methodological approach, namely a qualitative descriptive approach. The research data comes from the Hikayat text in the Buku Bahasa Indonesia Kelas X Kurikulum Merdeka. This analysis was carried out by reading the entire text and continuing with note-taking techniques, which functioned to record important points to find data in research analysis and continued to outline the material for further analysis. The results of this study found all types of endocentric phrases in the Hikayat text. In the entire text of the Hikayat that had been read, endocentric phrases were found based on their categories, namely 25 coordinating endocentric phrases, 80 attributive endocentric phrases, and 5 appositive phrases. The characteristics of the phrases obtained are based on their form, type, and structure. In this study, it was concluded that in determining the type of endocentric phrases, it can be analyzed by determining the categories of phrases based on the word class. For example, the equivalence of coordinating phrases can be determined based on word class and grammatical meaning, followed by phrases that express the same condition, conjunctive phrases, or no conjunctions. Then the attributive element in an attributive coordinating phrase is not always a word but can be a clitic as an explanatory element, both proclitic and enclitic. This analysis is intended to develop research in the analysis of types of endocentric phrases and to add knowledge and insight regarding endocentric phrases.